Evaluating the association between antidepressant dose trajectories and treatment augmentation in pediatric depression. Issue 2 (28th September 2021) - Spence, O'Mareen; Reeves, Gloria; dosReis, Susan
Abstract: Purpose: To identify antidepressant dose trajectories in the first 6‐months of antidepressant initiation and to evaluate the association between antidepressant dose trajectories and augmentation with another psychotropic medication. Methods: Using the IQVIA PharMetrics® Plus database, we identified 5655 commercially insured youth (3–18 years) with depression who newly initiated an antidepressant anytime from January 2007 to June 2015. No antidepressant use within 1 year prior to the index prescription defined new use. Latent class growth analysis of antidepressant dosing in the 6 months after initiation defined the exposure groups. The outcome was any regimen change, that is, antidepressant augmentation with another psychotropic or discontinuation of the antidepressant, with and without switching to another psychotropic. Baseline covariates measured in the 6 months before antidepressant initiation included demographic factors, psychiatric comorbidities, and health service use. Multinomial logistic regression tested the association between antidepressant dose trajectories and the odds of an antidepressant regimen change. Results: Five dose trajectories were sharp decline (n = 897; 16%), slow decline (n = 1029; 18%), stable minimum dose (n = 1397; 25%), stable maximum dose (n = 1783; 32%), and increasing high dose (n = 549; 10%). Relative to the stable minimum dose group, the sharp and slow decline groups were more likely to discontinue the antidepressant, either switch to another psychotropic (OR [odds ratio]: 5.91; 95%CI: 3.23–10.80 and OR: 1.67; 95%CI: 1.04–2.68, respectively) or stop all psychotropic medication (OR: 6.64; 95%CI: 4.24–10.39 and OR: 1.62; 95%CI: 1.22–2.13, respectively). However, the stable maximum and increasing high‐dose groups were less likely to discontinue, either switch (OR: 0.38; 95%CI: 0.24–0.61 and OR: 0.30; 95%CI: 0.16–0.59, respectively) or stop all psychotropic medications (OR: 0.15; 95%CI: 0.12–0.20 and OR: 0.02; 95%CI: 0.01–0.03 respectively) than augment with another psychotropic. Conclusions: The findings from this cross‐sectional study demonstrate an association between antidepressant dose trajectories within 6 months of initiating treatment and the odds of augmenting with another psychotropic.